Modeling and analysis of SIR epidemic dynamics in immunization and cross-infection environments: Insights from a stochastic model - Chang, Zhengbo; Meng, Xinzhu; Hayat, Tasawar; Hobiny, Aatef (Nonlinear Analysis: Modelling and Control, 2022)
We propose a stochastic SIR model with two different diseases cross-infection and immunization. The model incorporates the effects of stochasticity, cross-infection rate and immunization. By using stochastic analysis and Khasminski ergodicity theory, the existence and boundedness of the global positive solution about the epidemic model are firstly proved. Subsequently, we theoretically carry out the sufficient conditions of stochastic extinction and persistence of the diseases. Thirdly, the existence of ergodic stationary distribution is proved. The results reveal that white noise can affect the dynamics of the system significantly. Finally, the numerical simulation is made and consistent with the theoretical results.
Keywords: stochastic SIR model; nonlinear incidence rates; disease cross-infection; persistence in mean; ergodic stationary distribution